(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
The article explores the relationship between educational level and employability in Ecuador, comparing individuals with university and postgraduate education. Based on ENEMDU 2023 data, the analysis considers variables such as residence area, marital status, age, occupation, and poverty. The results indicate that postgraduate education significantly enhances job stability, income, and access to full employment while reducing poverty and extreme poverty rates. However, inequalities in access to advanced education persist, particularly among ethnic groups and rural populations. This study highlights the need for inclusive public policies to promote equity in higher education and maximize its impact on social and economic development.